Dinamika Konflik Agraria Perspektif Politik Hak Atas Tanah: Studi Kasus Atas Konflik Antara PT. Swarna Cinde Raya Dengan Warga Desa Pangkalan Benteng Kecamatan Talang Kelapa Kabupaten Banyuasin - Alya Rosalina; Taufik Akhyar; Hatta Azzuhri (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
This research discusses "The Dynamics of Agrarian Conflicts: Political Perspectives of Land Rights (Case Study of the Conflict Between PT. Swarna Cinde Raya with residents of Pangkalan Benteng Village, Talang Kelapa District, Banyuasin Regency)''. It aims to find out the causes and development of the dynamics of agrarian conflicts between the residents of Pangkalan Benteng Village and PT Swarna Cinde Raya. The research method used was qualitative. With primary data, namely residents of Pangkalan Benteng village, Banyuasin Regency. Data collection techniques through interviews and documentation. The results of the study show that first. The agrarian conflict between the residents of Pangkalan Benteng Village and PT Swarna Cinde Raya occurred due to overlapping land claims, land evictions by the company, and the slow response of the government and law enforcement. The main causes are ownership disputes, human rights violations, and lack of transparency in the resolution of cases by the authorities. Second, the agrarian conflict between the residents of Pangkalan Benteng Village and PT Swarna Cinde Raya (PT SCR) has been going on since 2009. PT SCR claims that the 200 hectares of land managed by residents for generations has now been reduced to 80 hectares. The company put up prohibition signs based on the Agrarian Cases Law, causing intimidation and uncertainty for residents. Residents feel that their rights have been deprived, suffered losses due to evictions, and have received a slow response from the government and law enforcement. South Sumatra's Ministry of Law and Human Rights recommends a settlement through legal channels, but the slow and lack of transparency creates public distrust and risks escalating conflicts. This conflict reflects structural problems of agrarian management in Indonesia, such as power imbalances, overlapping regulations, and weak protection of indigenous peoples' rights. A just settlement must prioritize transparency, community participation, and respect for human rights so that conflicts do not spread.